The Influence of Parenting Patterns on the Development of Adolescent Social Relations - Mario Mario (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2024)
This study explores the influence of parenting patterns on the development of adolescent social relations. Adolescence is a critical period for social development, where interactions with peers and adults significantly shape social skills and behaviors. The research aims to identify which parenting styles—authoritative, authoritarian, permissive, or uninvolved—most effectively promote positive social relationships among adolescents. Using a mixed-methods approach, data was collected through surveys, interviews, and observations of adolescents and their parents. The findings indicate that authoritative parenting, characterized by high responsiveness and demandingness, is most conducive to fostering healthy social relationships. Adolescents raised in authoritative households exhibit higher levels of social competence, better conflict resolution skills, and greater empathy compared to those from authoritarian, permissive, or uninvolved backgrounds. The study underscores the importance of adopting parenting practices that balance support and discipline to optimize adolescents' social development.